(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study represents how to mitigate street crimes in Barangay Gulod Novaliches Quezon City and provides an opportunity for the citizens of Barangay Gulod. It represents the solution to the insufficiency of the Barangay that can help the staff of the Barangay Officials do their duty. The aim of the researchers is to know what the most effective crime prevention methods are. This research can help the peace officer or the Public Officer maintain Peace and Order in the Barangay. The community can also benefit from This study on how to protect themselves from street crimes. To Sanguniang Barangay Gulod, The Researchers highly recommend focusing on sports and tournaments, which can be an effective Barangay Activity in promoting peace and order and, eventually, crime mitigation. The Researchers highly recommend foot patrol to monitor the effective implementation of curfew hours within the LGU jurisdiction. Future Researchers Understand well the effect and influence that will happen depending on the other parameters that can be connected to different classifications of crime intervention.